КОСТОМУКША – КРУПНЕЙШИЙ КОМПЛЕКСНЫЙ РУДНЫЙ ОБЪЕКТ РЕСПУБЛИКИ КАРЕЛИЯ - Горьковец, В.Я.; Максимович, Л.А.; Раевская, М.Б. (КНЦ РАН, 2011)
The background of the geological study of the Kostomuksha Ore Province, which includes various genetic types of polychromous ore formation, is discussed. Distinctive iron-cherty, gold and diamondiferous ore formations were generated in common geodynamic settings that succeeded each other in this territory from Neoarchaean to Neoproterozoic time (from 2.9 to 1.23 Ga) inclusive, and were associated with the uplift of the Voknavolok block above a mantle diapir (Deep structure .., 2001). Kontokki-series tholeiitic basalt, komatiites and felsic volcanics of rhyodacite composition intruded along the deep fault zones that rimmed the Voknavolok block in the Neoarchaean (2.9 -2.8 Ga). Two iron formations: a rhyodacitic iron-cherty formation and the most productive terrigenous (flysch) iron-cherty formation (Gimoly series) developed in the Neoarchaean. The rocks and ores of this formation were produced under areal chemical weathering crust conditions on a Palaeoarchaean granulitic basement and underlying Lopian Kontokki volcano-sedimentary units, and are represented by the Kostomuksha iron deposit, which has the biggest iron ore reserves (over 10 billion t) in the Fennoscandian Shield. As the iron ore reserves of the deposit relative to the proved iron ore reserves of the world deposits are rated at 1.04%, it is considered a superlarge deposit (Gorkovets & Rayevskaya, 2004).
KOSTOMUKSHA – THE LARGEST COMPLEX ORE PROVINCE OF THE REPUBLIC OF KARELIA
Keywords: Костомукша